Etiologies of Persistent Aminotransferase Elevations in Chronic Hepatitis B Patients Treated with Nucleos(t)ide Analogs - Xiong, Qing-Fang; Zou, Lei; Chen, Zi-Jie; Liu, Hong-Li; Lu, Yu-Jia; Liu, Du-Xian; Yang, Yong-Feng (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Recent studies revealed that patients with persistent aminotransferase elevations after antiviral treatment had higher risk of hepatic events; yet its underlying causes remain unclear. Our study aimed to investigate the etiologies of persistent aminotransferase elevations in patients treated with nucleos(t)ide analogs (NAs). Materials and Methods: A retrospective study was conducted on chronic hepatitis B (CHB) patients who had been receiving NA treatment for over a year and had an aminotransferase level greater than 40 IU/mL (more than twice, with a 3-month interval) and subsequently underwent a liver biopsy. Results: The study group included 46 patients (34 males) with a mean age of 44.8 ± 20.3 years (range: 24-71 years).The average duration of NA therapy was 3.7 years (1.1-10.6 years). The etiologies of persistant transaminase elevation were categorized into 4 groups: patients with low hepatitis B virus (HBV) viral load (LVL, n = 11); concurrent non-alcoholic fatty liver disease (NAFLD, n = 12); concurrent other liver diseases (OLD, n = 12); and unknown liver dysfunction (ULD, n = 11). The proportion of G ≥ 2 inflammation was significantly higher in the LVL group (90.9%) compared to NAFLD (33.3%), OLD (50%), and ULD (27.2%) groups (P = .012). The hepatitis B e-antigen (HBeAg)-positive group exhibited a younger age (34.5 ± 10.2 vs. 48.1 ± 9.4 years, P < .001), a lower proportion of fibrosis F ≥ 2 (36.3% vs. 77.1%, P = .012), and a higher prevalence of detectable HBV DNA (54.5% vs.14.2%, P = .00632) compared to the HBeAg-negative group. Conclusion: The etiology of persistent aminotransferase elevations in CHB patients undergoing NAs treatment warrants investigation. Besides the commonly observed NAFLD and low HBV viral load, concurrent presence of other liver diseases requires elucidation.The proportion of G≥2 inflammation was higher in the LVL group. Cite this article as: Xiong Q, Zou L, Chen Z, et al. Etiologies of persistent aminotransferase elevations in chronic hepatitis B patients treated with nucleos(t)ide analogs. Turk J Gastroenterol. 2024;35(6):497-504.